2015
DOI: 10.5539/apr.v7n6p61
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Bacterial Diseases in Rice Plants Leaves by the Use of Spectroscopic Imaging

Abstract: Rice is staple in the African habitats menu. Bacterial wilt (BLB) and leaf streak (BLS) are some of the phytopathological diseases which restrain rice production around the world. In this paper, multi-spectral and multimodal imaging techniques have been developed to characterize the rice leaves with symptoms of bacterial wilt (BLB) and leaf streak (BLS), and to provide information on their effects, in order to reduce their spread. First, we recorded microscopic and spectroscopic images of the samples using mul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 15 publications
0
4
0
Order By: Relevance
“…In the measurement of the reflectance, the alignement of optics in the microscope and fixation of its focal plan at the reference wavelength being done during the measures in transmission mode, we active the geometry "reflection" inthe Lab view code interface in order to run the automated acquisition of the thirteen images.The signal s R ismeasuredafter having put the slide containing the sample on the microscope's holder.The signal b R is acquiredby usinga diffuser in the place of the sample, with its white face upin the microscope. The diffuser eliminates dissymetry light dispatching andallows anuniform intensity distributionin the camera's field of theview [3]. To acquire the image, d R , the microscope's holder is kept empty in order to get parasite reflection dueto the opticsin the microscope.…”
Section: Measurement's Proceduresmentioning
confidence: 99%
See 1 more Smart Citation
“…In the measurement of the reflectance, the alignement of optics in the microscope and fixation of its focal plan at the reference wavelength being done during the measures in transmission mode, we active the geometry "reflection" inthe Lab view code interface in order to run the automated acquisition of the thirteen images.The signal s R ismeasuredafter having put the slide containing the sample on the microscope's holder.The signal b R is acquiredby usinga diffuser in the place of the sample, with its white face upin the microscope. The diffuser eliminates dissymetry light dispatching andallows anuniform intensity distributionin the camera's field of theview [3]. To acquire the image, d R , the microscope's holder is kept empty in order to get parasite reflection dueto the opticsin the microscope.…”
Section: Measurement's Proceduresmentioning
confidence: 99%
“…Zoueu et al [1] have shown that using multispectral imaging allows detecting malaria without using fluorescent labels for parasites as it is the case of thick and thin blood smears. Multispectral imaging is an important tool in the delimitation of reserved forests [2] and also in agriculture framework for rapid detection of fruit diseases [3] [4].…”
Section: Introductionmentioning
confidence: 99%
“…This system was utilised as an alternative tool for staining-free malaria diagnosis. [12][13][14] The same instrument was also used to study, analyse, predict and build statistical models of infected tropical plant leaves [15][16][17] to enhance agricultural production. The potential of this optical microscope to spectrally differentiate and classify the samples' content also made it a valuable tool for biological diagnostic approaches.…”
Section: Introductionmentioning
confidence: 99%
“…Several methods exist for monitoring the health of plants [5] [11] [12] and are based on the interaction between light and matter. Multi-spectral imaging [13] [14] [15] and fluorescence [16] [17] [18] have also shown their ability to monitor the health of plants and to discriminate against certain diseases. We combine these two techniques to discriminate two types of maize plant (healthy and treated with herbicide plants) to predict the physiological state of a new database and especially to understand the impact of the herbicide on the physiology of the plant.…”
Section: Introductionmentioning
confidence: 99%